Resistance of Ten Local Rice Cultivars From Central Sulawesi to Nephotettix virescens (Hemiptera: Cicadellidae) - Asrul, Asrul; Wahid, Abd.; Zulkifly, Zulkifly; Arsih, Desi Wahyuni (Universitas Tadulako, 2025)
The green leafhopper (Nephotettix virescens) is the primary vector of the tungro virus, posing a significant threat to rice productivity in Indonesia. The utilization of local cultivars with natural resistance represents a sustainable strategy to mitigate such biotic constraints. This study aims to evaluate the resistance levels of ten local rice cultivars from Central Sulawesi against N. virescens using the International Rice Research Institute (IRRI) standard evaluation. The assessment covers parameters such as incubation period, symptom severity, and disease index (DI) to classify phenotypes and recommend priority genotypes. The research was conducted from April to September 2025 at the Plant Pest and Disease Green House, Faculty of Agriculture, Tadulako University, utilizing a Randomized Block Design (RBD) with three replications. The ten cultivars tested originated from Ampana (Gondu, Masai, Kamba Bulili, and Kalendeng), Sigi (PM and Kas), and Banggai (Habo, Sampara, Dongan, and Uva Buya). Results indicated that the symptom incubation period ranged from 5 to 7 days after infection (DAI). Based on the disease index (DI) observed from 14 to 56 DAI, significant genetic response diversity was found among the cultivars. The cultivar Kamba Bulili was classified as resistant with the lowest DI value of 3.8. In contrast, the cultivars Kas (DI 7.4) and PM (DI 7.0) were categorized as susceptible. The remaining seven cultivars exhibited a rather resistant response.